Virtual Connections: Improving Global Neurosurgery Through Immersive Technologies - Higginbotham, George (Frontiers in Surgery, 2021)
The field of neurosurgery has always been propelled by the adoption of novel technologies to improve practice. Although advancements have occurred in the diagnosis, treatment, and long-term outcomes of patients, these have not translated to global patient benefit. Up to 5 million people each year do not have access to safe and affordable neurosurgical interventions, and those in low- and middle-income countries (LMIC) are disproportionately affected. Current approaches to increase neurosurgical capacity are unlikely to meet the UN Sustainable Development Goals target by 2030, and many of the most successful programs have been disrupted by the travel restrictions of the COVID-19 pandemic. There is therefore a pressing need for creative virtual solutions. An area of growing relevance is the use of immersive technologies: virtual reality (VR) and augmented reality (AR). AR allows additional information to be superimposed onto the surgeon’s visual field, thus enhancing intra-operative visualisation. This can be used for remote tele-proctoring, whereby an experienced surgeon can virtually assist with a procedure regardless of geographical location. Expert guidance can therefore be given to both neurosurgical trainees and non-neurosurgical practitioners, further facilitating the growing practice of neurosurgical task-shifting in LMIC. VR simulation is another useful tool in remote neurosurgical training, with the potential to reduce the learning curve of complex procedures whilst conserving supplies in low-resource settings. The adoption of immersive technologies into practice is therefore a promising approach for achieving global neurosurgical equity, whilst adapting to the long-term disruptions of the pandemic.